Tantangan Gnostik bagi Hidup Beriman Masa Kini - Purwatma, Matheus (Jurnal Orientasi Baru, 2012)
Since the beginning of the Christianity, Gnosticism is a challenge to the Christian faith. The Church’s Fathers called gnostic a source of all heretics. Generally, gnostic has a dualistic system; good-evil, light-darkness, world of pleroma – material world. The True God is completely transcendent. The universe is created by the lower God, and belongs to the material world. Human being is a composite nature, created by by the lower God but has a divine spark within. Through the achievement of gnosis human being can liberate the divine spark from the prison of the material world. In gnostic system Jesus Christ is a Messenger of Light who teaches gnosis to his disciple. His role is not other than a teacher who helps his disciple to know gnosis. Nowadays, gnostic system appears in some psychological practices, meditation and spiritual movement centered on the self-manifestation.